Impact of Covid-19 Infection on Pregnancy: Scoping Review - Tezi Kharina Aprezia; Mohammad Hakimi; Herlin Fitriani Kurniawati (Syntax Corporation Indonesia, 2022)
The current COVID-19 pandemic is considered an example of a natural disaster with so much global health burden, over 22 million people worldwide contracted it and more than 791,000 people died. The purpose of compiling this Scoping Review is to obtain evidence based and case descriptions, impacts, vertical transmission of Covid-19 infection in pregnant women. Using Scoping Review data obtained from Pubmed, ScienceDirect and Ebscohost. Furthermore, an assessment and mapping of themes is carried out. An article that discusses COVID-19 infection in pregnant women. There are patients who experience the most common symptoms such as cough and fever, there are pregnancy impacts from pregnant women who are positive for COVID-19 such as abortion, premature birth, Caesarean section and death. There is no vertical transmission from mother to fetus. Pregnant women are susceptible to severe illness in case of viral infection. There are impacts of COVID-19 infection on pregnancy including abortion, premature, caesarean section and death. There is no vertical transmission from mother to fetus.